Visceral osteopathic manipulative treatment reduces patient reported digestive toxicities induced by adjuvant chemotherapy in breast cancer: A randomized controlled clinical study. (October 2019) - Lagrange, Aurélie; Decoux, Damien; Briot, Nathalie; Hennequin, Audrey; Coudert, Bruno; Desmoulins, Isabelle; Bertaut, Aurélie
Abstract: Objective: Breast cancer patients often benefit from adjuvant chemotherapy, a protocol whose effectiveness is accompanied by disabling adverse effects. The aim of this controlled clinical study was to determine the impact of visceral osteopathy on the incidence of nausea/vomiting, constipation and overall quality of life (QoL) in women operated for breast cancer and undergoing adjuvant chemotherapy in Centre Georges François Leclerc, CGFL. Study Design: Ninety-four women operated for a breast cancer stage 1–3, in complete resection and to whom a 3 FEC 100 chemotherapy was prescribed, were randomly allocated to experimental or placebo group. Experimental group underwent a visceral osteopathic technique and placebo group was subjected to a superficial manipulation after each chemotherapy cycle. Rate of grade ≥1 nausea/vomiting or constipation, on the first 3 cycles of FEC 100, were reported. QoL was evaluated using the EORTC QLQ-C30 questionnaire. Results: Rate of nausea/vomiting episodes of grade ≥1 was high in both experimental and placebo group. Constipation episodes of grade ≥1 were also frequent. No significant differences were found between the two groups concerning the rate of nausea/vomiting (p = 0.569) or constipation (p = 0.204) according to clinician reported side-effects but patient reported impact of constipation and diarrhoea on quality of life was significantly lower in experimental group (p = 0.036 and p = 0.038, respectively). Conclusion: Osteopathy does not reduce the incidence of nausea/vomiting in women operated for breast cancer and undergoing adjuvant chemotherapy. In contrast, patient reported digestive quality of life was significantly ameliorated by osteopathy. Clinicaltrials.gov Identifier: NCT02840890.